2015
DOI: 10.3390/catal5041673
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Coated Film Catalyst Layer Model to a High Temperature Polymer Electrolyte Membrane Fuel Cell with Low Catalyst Loading Produced by Reactive Spray Deposition Technology

Abstract: Abstract:In this study, a semi-empirical model is presented that correlates to previously obtained experimental overpotential data for a high temperature polymer electrolyte membrane fuel cell (HT-PEMFC). The goal is to reinforce the understanding of the performance of the cell from a modeling perspective. The HT-PEMFC membrane electrode assemblies (MEAs) were constructed utilizing an 85 wt. % phosphoric acid doped Advent TPS ® membranes for the electrolyte and gas diffusion electrodes (GDEs) manufactured byRe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…In addition, the fuel cell performance is also strongly influenced by the composition and fabrication protocols of MEA. A semiempirical model was developed by Myles et al to understand the performance of the cell as a function of the ratio of Nafion ionomer to carbon support (I/C ratio) in high temperature PEMFCs [31].…”
Section: This Special Issuementioning
confidence: 99%
“…In addition, the fuel cell performance is also strongly influenced by the composition and fabrication protocols of MEA. A semiempirical model was developed by Myles et al to understand the performance of the cell as a function of the ratio of Nafion ionomer to carbon support (I/C ratio) in high temperature PEMFCs [31].…”
Section: This Special Issuementioning
confidence: 99%
“…At present, only a few studies have been conducted in this regard. Notable among them are focused on advanced catalyst-deposition techniques, such as sputter deposition, 6 ultrasonic spraying, 7 electrospraying, 8 and reactive spray deposition technology, 9,10 to tailor the catalyst layers. These processes usually generate a high concentration of Pt in the catalyst layers.…”
Section: Introductionmentioning
confidence: 99%
“…From the results we concluded that additional effects of reaction inhibition could play a role, which might involve building up of a mass transport limiting barrier at the electrode-electrolyte interface. Aside from processes at the interface, the solubility and diffusivity of dissolved gaseous reactants in the bulk of highly concentrated PA are important parameters to characterize the reactant mass transport in fuel cell electrodes [12][13][14][15]. Mass transport of reactant gases in electrode layers of PAFC and PEMFC is generally considered by thin-film models suggesting a surface coverage of catalyst particles or agglomerates with electrolyte films that have bulk properties [9,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%